(untitled) (Research, Society and Development, 2022)
The present work aimed to carry out a critical analysis of the advances and challenges experienced in the restructuring process of the Food Bank in the city of Natal/RN. It was characterized as an exploratory, qualitative and quantitative case study regarding the challenges of structuring the Food Bank Program in the city of Natal/RN. Data collection by documentation was carried out at the Department of Food Security of Natal, linked to SEMTAS, through the collection of information present in physical and digital files, containing records of the operation of the Food Bank since the moment of its implementation. in the city of Natal, from 2006 to the present day. The Food Bank Program in the municipality of Natal has historically faced a path full of obstacles. Although the Restructuring process started in 2022, has allowed a significant evolution, representing a leap in quality in its operation and in the expansion of its performance, contributing to the minimization of the situation of food insecurity in a much greater proportion, there is still a There is a long way to go to continue in the direction of potentiating their actions, solving the difficulties reported. A fact that will only be possible with the effective performance of public management in strengthening strategies consistent with the implementation of the Food Security Policy at the municipal level.